2022
DOI: 10.3389/fnhum.2022.890483
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Working Memory Representations in the Left Inferior Parietal Lobe in the Face of Distraction and Neural Stimulation

Abstract: The neural basis of phonological working memory (WM) was investigated through an examination of the effects of irrelevant speech distractors and disruptive neural stimulation from transcranial magnetic stimulation (TMS). Embedded processes models argue that the same regions involved in speech perception are used to support phonological WM whereas buffer models assume that a region separate from speech perception regions is used to support WM. Thus, according to the embedded processes approach but not the buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…3d), whereas in the SMG, the opposite was the case (Fig. 3e; see also [74,76] for similar evidence using multi-voxel pattern analysis (MVPA) and transcranial magnetic stimulation (TMS)). On the other hand, semantic representations could not be decoded in either STG or SMG during either encoding or maintenance, showing the specificity of these regions for phonological WM.…”
Section: Domain-generality In Neural Substratesmentioning
confidence: 64%
See 1 more Smart Citation
“…3d), whereas in the SMG, the opposite was the case (Fig. 3e; see also [74,76] for similar evidence using multi-voxel pattern analysis (MVPA) and transcranial magnetic stimulation (TMS)). On the other hand, semantic representations could not be decoded in either STG or SMG during either encoding or maintenance, showing the specificity of these regions for phonological WM.…”
Section: Domain-generality In Neural Substratesmentioning
confidence: 64%
“…Although parietal regions have been implicated in both visual and verbal WM, different parts of the parietal lobe have been identified in these two domains. Specifically, the bulk of evidence in visual WM points to posterior parietal and intraparietal sulcus (IPS), whereas verbal WM studies often implicate the supramarginal gyrus (SMG) [67][68][69][70][71][72][73][74][75][76]. Even within the domain of language processing, researchers have identified separable neural correlates for semantic and phonological WM [77].…”
Section: Domain-generality In Neural Substratesmentioning
confidence: 99%
“…Critically, decoding was still possible in SMG. In a second experiment, the authors showed that transcranial magnetic stimulation to SMG, but not STG, disrupted phonological working memory (Yue & Martin, 2022). These results provide support for the buffer account.…”
Section: Links To Other Debates Regarding Working Memory In Language ...mentioning
confidence: 78%
“…The MFG has been recognized to be crucial for maintaining information and supporting executive function during WM, especially high-load WM tasks (Volle et al, 2008;Bokde et al, 2010). The IPL was believed to play a critical role in maintaining phonological representations during phonological WM (Yue and Martin, 2022). It has been demonstrated that the cerebellum was included in the WM network and played a relevant role in subvocal rehearsal (Pleger and Timmann, 2018).…”
Section: Discussionmentioning
confidence: 99%